The Typology of The Kost-Shop Friendly Facades in The Reproduction of Social Interaction Space based on The Needs and Opportunities between Kampung and Campus - Pasaribu, Ramos Panondang; Tobing, Rumiati R; Siahaan, Uras (Jurnal Teknik Sipil dan Perencanaan, 2020)
One interesting phenomenonÂ  found in Indonesia to date is â€œliving and growing in a city with the characteristic features of a Kampung (urban village) with all of its distinctive facesâ€, like the interdependent relations between the Kampung Kemanggisan around the Syahdan Campus of Bina Nusantara Jakarta. The students find their daily needs in the Kampung and the villagers find business opportunities and reproduce the â€œSocial Interaction Spaceâ€ along the Haji Senin street (study location) which is dominated by buildings with the ground floor as a place of business and the upper floor as a Kost or the private housings with rented rooms which in this study was called the â€œKost-Shopâ€ building. Variations of the â€œPedestrian-Friendly Kost-Shopâ€ building grew and had an impact on the appearance of the facade. This study to reveal and provides an understanding of typology of â€œKost-Shop Friendly Facadesâ€ that exists based on student â€œNeeds and the Opportunitiesâ€, therefore, this study was written with the title of â€œKost-Shop Facadesâ€ in â€œthe Reproduction of Social Interaction Spaceâ€ based on the â€œNeeds and Opportunitiesâ€ between Kampung and Campus. By using qualitative research methods; case study with indications of â€œsocial, permeable, activeâ€ obtained 12 types of â€œKost-Shop Friendly Facadesâ€.